Intersectionality and Its Impact on Microaggression in Female Physicians in Academic Medicine: A Cross-Sectional Study - Alyson K. Myers; Myia S. Williams; Renee Pekmezaris (Mary Ann Liebert, 2023)
Introduction: The burden of microaggressions in the workplace is an ongoing stressor for female physicians in academic medicine. For female physicians of Color or of the Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual community, this burden is even heavier due to the concept of intersectionality. The goal of this study is to assess frequency of microaggressions experienced by participants. In addition, to explore the associations between microaggression and individual outcomes, patient care practices and attitudes, and perception of pay/promotion equity. Methods: This was a cross-sectional analysis of female residents, fellows and attendings conducted from December 2020?January 2021 at Northwell Health across all specialties. One hundred seventeen participants replied to the study in REDCap. They completed questionnaires related to the topics of imposter phenomenon, microaggressions, gender identity salience, patient safety, patient care, counterproductive work behavior and pay and promotion equity. Results: A majority of the respondents were white (49.6%) and 15+ years out of medical school (43.6%). Around 84.6% of female physicians endorsed experiencing microaggressions. There were positive associations between microaggressions and imposter phenomenon as well as microaggressions and counterproductive work behavior. There was a negative association between microaggressions and pay equity or promotion. The small sample size did not allow for us to examine differences by race. Discussion: Although the number of female physicians continues to rise due to an uptick in female medical school enrollees, female physicians still must deal with the burden of microaggressions in the workplace. Conclusions: As a result, academic medical institutions must seek to create more supportive workplace for female physicians.